Answer:
The two factors will be
Step-by-step explanation:
We have given the equation ![9-16x^4](https://tex.z-dn.net/?f=9-16x%5E4)
We know the algebraic equation ![a^2-b^2=(a+b)(a-b)](https://tex.z-dn.net/?f=a%5E2-b%5E2%3D%28a%2Bb%29%28a-b%29)
As
can be written as
, as square of 3 is 9 and square of
is ![16x^4](https://tex.z-dn.net/?f=16x%5E4)
So ![9-16x^4=3^2-(4x^2)^=(3+4x^2)(3-4x^2)](https://tex.z-dn.net/?f=9-16x%5E4%3D3%5E2-%284x%5E2%29%5E%3D%283%2B4x%5E2%29%283-4x%5E2%29)
So the two factors will be ![=(3+4x^2)\ and\ (3-4x^2)](https://tex.z-dn.net/?f=%3D%283%2B4x%5E2%29%5C%20and%5C%20%283-4x%5E2%29)
The answer is C
i think so
if 35 is LESS than 39
so +35 - 39 is -4 F°
the answer to the freezing point of (hehe) butter is -4 F°
Answer:
Number one will be 11 minutes
Number two will be 525 words
Step-by-step explanation:
Answer:
![\large\boxed{f'(x)=\dfrac{12x^2}{\sqrt{2x^3-1}}}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7Bf%27%28x%29%3D%5Cdfrac%7B12x%5E2%7D%7B%5Csqrt%7B2x%5E3-1%7D%7D%7D)
Step-by-step explanation:
![f(x)=4\sqrt{2x^3-1}=4\left(2x^3-1\right)^\frac{1}{2}\\\\f'(x)=4\cdot\dfrac{1}{2}(2x^3-1)^{-\frac{1}{2}}\cdot3\cdot2x^2=\dfrac{12x^2}{(2x^3-1)^\frac{1}{2}}=\dfrac{12x^2}{\sqrt{2x^3-1}}\\\\\text{used}\\\\\sqrt{a}=a^\frac{1}{2}\\\\\bigg[f\left(g(x)\right)\bigg]'=f'(g(x))\cdot g'(x)\\\\\bigg[nf(x)\bigg]'=nf'(x)\\\\(x^n)'=nx^{n-1}](https://tex.z-dn.net/?f=f%28x%29%3D4%5Csqrt%7B2x%5E3-1%7D%3D4%5Cleft%282x%5E3-1%5Cright%29%5E%5Cfrac%7B1%7D%7B2%7D%5C%5C%5C%5Cf%27%28x%29%3D4%5Ccdot%5Cdfrac%7B1%7D%7B2%7D%282x%5E3-1%29%5E%7B-%5Cfrac%7B1%7D%7B2%7D%7D%5Ccdot3%5Ccdot2x%5E2%3D%5Cdfrac%7B12x%5E2%7D%7B%282x%5E3-1%29%5E%5Cfrac%7B1%7D%7B2%7D%7D%3D%5Cdfrac%7B12x%5E2%7D%7B%5Csqrt%7B2x%5E3-1%7D%7D%5C%5C%5C%5C%5Ctext%7Bused%7D%5C%5C%5C%5C%5Csqrt%7Ba%7D%3Da%5E%5Cfrac%7B1%7D%7B2%7D%5C%5C%5C%5C%5Cbigg%5Bf%5Cleft%28g%28x%29%5Cright%29%5Cbigg%5D%27%3Df%27%28g%28x%29%29%5Ccdot%20g%27%28x%29%5C%5C%5C%5C%5Cbigg%5Bnf%28x%29%5Cbigg%5D%27%3Dnf%27%28x%29%5C%5C%5C%5C%28x%5En%29%27%3Dnx%5E%7Bn-1%7D)